Étude comparative du développement de la capacité narrative orale d’enfants francophones de milieux minoritaire et majoritaire - Allard, Suzanne (Canadian Journal of Applied Linguistics, 2004)
This study compares the development of oral communicative competence in Francophone children aged 7, 9 and 11 living in minority and majority settings. A corpus of 147 narratives was analysed using a functional approach. This approach reveals the various syntactical and discursive forms used by the children to express a given communicative function when telling a story. The episodic structure of a picture book (Frog, where are you?) was presented to the children as a stimulus. This episodic structure was based on Bamberg and Marchman (1994), who validated a schematization of the same text. The results describe linguistic characteristics of Acadian children’s language other than the usual sentence-level features.